1997
DOI: 10.1046/j.1365-2249.1997.4211317.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of granulocyte colony-stimulating factor (G-CSF) in a granulocytopenic mouse model of Pseudomonas aeruginosa lung infection through enhanced phagocytosis and killing by alveolar macrophages through priming tumour necrosis factor-alpha (TNF-α) production

Abstract: SUMMARYWe investigated the effects of G-CSF in a granulocytopenic mouse model of Pseudomonas aeruginosa lung infection. The model was prepared by intratracheal instillation of the bacteria, while granulocytopenia was induced by intraperitoneal injection of 4 . 0 mg of cyclophosphamide (CPA). There was no difference in the survival rate between G-CSF-treated animals and the normal group, and the number of neutrophils in the blood and lung recovered to normal in the former group. However, the phagocytic and kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
5
15
0
Order By: Relevance
“…Furthermore, our studies indicated that intrapulmonary TNF expression in vivo enhanced the ability of AM to ingest P. aeruginosa when cultured ex vivo. Similar effects of TNF on macrophage phagocytic activity have been shown by others (61). The mechanism for enhanced phagocytic function in response to in vivo expression of the TNF transgene remains unclear, as we observed no significant change in the expression of several AM cell surface molecules involved in the phagocytic response, including CD54, CD11b, CD11c, and CD16 (data not shown).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our studies indicated that intrapulmonary TNF expression in vivo enhanced the ability of AM to ingest P. aeruginosa when cultured ex vivo. Similar effects of TNF on macrophage phagocytic activity have been shown by others (61). The mechanism for enhanced phagocytic function in response to in vivo expression of the TNF transgene remains unclear, as we observed no significant change in the expression of several AM cell surface molecules involved in the phagocytic response, including CD54, CD11b, CD11c, and CD16 (data not shown).…”
Section: Discussionsupporting
confidence: 89%
“…[1][2][3][4] Indeed, experimental studies carried out by us (data not shown) and others [7][8][9] demonstrate that mice subjected to a CP regimen easily succumb to pulmonary gram-negative bacterial infection elicited by otherwise nonlethal inocula of bacteria. It has long been believed that granulocytopenianeutropenia is the only cause of such increased susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been believed that granulocytopenianeutropenia is the only cause of such increased susceptibility. [7][8][9] Lung tissue residential macrophages, however, are also an integral part of innate immunity, 19,30 and the lack of these cells, regardless of a normal level of peripheral blood neutrophils, predisposes hosts to acute lung bacterial infection. [12][13][14] The critical requirement of a normal number of AMs in the lung for innate immunity was further demonstrated in a recent study by Broug-Holub et al 15 showing that the host deficient in AMs succumbed to Klebsiella pneumonia despite a higher than normal level of neutrophilic infiltration in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…These toxic metabolites have been shown to reduce lung microsomal enzyme activity and decrease antioxidant defenses (29). Studies with Pseudomonas aeruginosa demonstrated that pretreatment of mice with CYP did not affect the ability of isolated AMs to phagocytize bacteria (34) and control B6 iNOS ϩ/ϩ mice were pretreated with CYP or saline i.p. and infected intranasally with 1.5 ϫ 10 7 CFU of M. pulmonis.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were injected i.p. with 200 mg of CYP (Bristol-Myers Squibb, Princeton, N.J.)/kg (ϳ4 mg) (26,34) and again 72 h later with 100 mg of CYP/kg (ϳ2 mg) i.p. Control mice were injected with sterile saline.…”
Section: Methodsmentioning
confidence: 99%